Effect of ZnO Filler on PVA-Alkaline Solid Polymer Electrolyte for Aluminum-Air Battery Applications. Issue 11 (14th August 2018) - Mokhtar, Marliyana; Majlan, Edy Herianto; Ahmad, Azizan; Tasirin, Siti Masrinda; Daud, Wan Ramli Wan
Abstract : Aluminum-air battery is a promising future energy storage device because it has a high energy density and is eco-friendly. The effects of zinc oxide filler on polyvinyl alcohol/alkaline solid polymer electrolyte for aluminum-air battery applications have been investigated. From the impedance measurement, the highest ionic conductivity achieved was 1.61 × 10 −2 S cm −1 by PVA/4 wt% ZnO/2 M KOH at room temperature. From XRD analysis, crystallinity intensity decreased when KOH was added into the system. The FTIR also showed that the O-H and C-O bonds shifted to a high wavenumber, from 3282 to 3383 cm −1 and 1092 to 1103 cm −1, respectively, as the KOH concentration increased, which strengthened the bonding in the film. Thus, LSV analysis showed that the highest stability achieved by PVA/4 wt% ZnO/2 M KOH was ±2.15 V, which proved that this film is suitable in aluminum-air battery applications. Furthermore, in the aluminum-air coin cell, the longest discharge voltage time was achieved by PVA/4 wt% ZnO/2 M KOH in which the cell voltage was maintained at 1.49 to 1.53 V for almost 20 hours at 0.8 mA/cm 2 .